Unrelated and related donor transplantation for beta‐thalassemia major: A single‐center experience from India. (3rd May 2018) - John, M. Joseph; Mathew, Amrith; Philip, Chepsy C.; Singh, Sohan; Tanuja, Tanuja; Kakkar, Naveen
Abstract: Hematopoietic stem cell transplantation (HSCT) remains the only curative treatment in patients with β‐thalassemia major. A matched sibling or a related donor is usually found in only 25%‐30% of the patients. There are limited data on matched unrelated donor (MUD) transplants from India. We reviewed HSCT outcome in 56 children with TM who underwent 57 transplants at our center. Related donor (RD) (n=43) and MUD (n=14) transplants were performed with TreoFluT‐based conditioning regimen in majority (95%) of patients. Peripheral blood stem cells (PBSC) were the preferred (85%) source of stem cells. The overall survival (OS) at 1 year in RD and MUD groups was 87.6±5.2% and 85.7±9.4% at a median follow‐up of 25 (1‐92) months and 22.5 (1‐50) months, respectively ( P =.757). The thalassemia‐free survival (TFS) at 1 year was 87.6±5.2% and 77.1±11.7% with a median follow‐up of 24 (1‐92) and 16.5 (1‐50) months, respectively ( P =.487). Although acute (14% vs 64%) and chronic graft‐versus‐host disease (GVHD) (13.9% vs 42.9%), infectious (39.5% vs 71.4%), and non‐infectious (37.2% vs 78.5%) complications are higher in MUD transplant group, the present data show a comparable OS and TFS among RD and MUD group with treosulfan‐based regimen using PBSC grafts.